2019
DOI: 10.3171/2018.4.jns171525
|View full text |Cite
|
Sign up to set email alerts
|

Results of Gamma Knife anterior capsulotomy for refractory obsessive-compulsive disorder: results in a series of 10 consecutive patients

Abstract: OBJECTIVE Obsessive-compulsive disorder (OCD) is a severe psychiatric condition. The authors present their experience with Gamma Knife radiosurgery (GKRS) in the treatment of patients with OCD resistant to any medical therapy. METHODS Patients with severe OCD resistant to all pharmacological and psychiatric treatments who were treated with anterior GKRS capsulotomy were retrospectively reviewed. These patients were submitted to a physical, neurological, and neuropsychological examination together with structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Recent reports have shown that GPi-DBS combined with capsulotomy is associated with significant long-term improvements which is quickly be evident in the patients’ TS symptoms and psychiatric comorbidities, along with sustained improvements in adaptive function and quality of life [17, 18, 31]. The temporary side effects such as weight gain, apathy, fatigue, and confusion, as well as, childish behaviors can occur after capsulotomy [32, 33]. In this study, we retrospectively assessed the clinical outcomes of several patients with severe and medication-refractory TS and psychiatric comorbidities who had been treated with bilateral GPi-DBS combined with capsulotomy but who intentionally or accidentally experienced a discontinuation of DBS during their treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that GPi-DBS combined with capsulotomy is associated with significant long-term improvements which is quickly be evident in the patients’ TS symptoms and psychiatric comorbidities, along with sustained improvements in adaptive function and quality of life [17, 18, 31]. The temporary side effects such as weight gain, apathy, fatigue, and confusion, as well as, childish behaviors can occur after capsulotomy [32, 33]. In this study, we retrospectively assessed the clinical outcomes of several patients with severe and medication-refractory TS and psychiatric comorbidities who had been treated with bilateral GPi-DBS combined with capsulotomy but who intentionally or accidentally experienced a discontinuation of DBS during their treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions used were ALIC DBS, 41,42 RF cingulotomy, 40,43 RF capsulotomy 45 and gamma-knife radio surgery capsulotomy. 44 Although all 7 studies addressed the concept of preoperative imaging predictors of response, only those by Rauch and colleagues 39 and Banks and colleagues 43 were primarily aimed at identifying preoperative neuroimaging predictors of response.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…Spatola and colleagues 44 reported a series of 10 patients with OCD who underwent gamma-knife radiosurgery capsulotomy. The authors reported that there were no correlations between imaging features and clinical improvement.…”
Section: Detailed Description Of Included Studiesmentioning
confidence: 99%
“…Moreover, SRS using LGK ICON™ also allows for frameless radiosurgery using a mask instead of a stereotactic frame while performing single fraction or hypofractionnated radiosurgery in well-selected cases [33]. Nowadays, the clinical applications of GKRS include benign and malignant tumors of the brain and skull-base [6,8,20,34], vascular malformations[9, 21], functional [11,12,24,36] and psychiatric [25] disorders. The intimate mechanisms of action may differ according to the treated condition and the targeting strategy: tumors -apoptosis [27][28][29]; vascular malformations -vessels obliteration by thrombotic endothelial proliferation [30][31][32]; functional procedures -targeting a specific anatomical point in an anatomical structure (e.g.…”
Section: Stereotactic Radiosurgery (Srs) Was Developed By the Swedishmentioning
confidence: 99%